Introduction to mechanical engineering: thermodynamics and strength of material - Chandra, Suresh (New Age, 2002)
Introduction to mechanical engineering: thermodynamics and strength of material / Chandra, Suresh. -- New delhi: New Age, 2002 620.1 C456e2 2nd ed. No. of Copies : 1